RESERVOIR Z7 IN FIELD X DEVELOPMENT STUDY WITH SIMULATION & ECONOMIC ANALYSIS - RUSMIYATI MARISA SINLAE, ESTERLINDA
Reservoir Z7 in field X is placed at Sumatera Utara Basin. Zone Z7 is devided into nine block separated with fault with almost all of them are leaking except fault berween block A and B and between block D4 and E which are sealing. Driving mechanism of these zones are strong water drive which production is starting at January 1, 1938 and ending at year 2003. The purpose of this research is to determine performance and location of hydrocarbon remained in zone Z7. Therefore we can optimize filed development with appropriate strategy and economic analysis using crude light oil price assumption between US$ 60/bbl-US$ 100/bbl and 40% inclining declining of production sensitivity analysis. Simulation software used is CMG (Computer Modeling Group) and economic calcuation software used is Fieldma (Field Management). IOIP initilaization result is 61,303 MSTB and IOIP from geologic model is 61,713 MSTB or there is difference 0.67 %. Primary drainage obtained is 32.82%. There three scenarios developed are: 1. Scenario-1 (Base case / Existing), cumulative production obtained is 24.922 MSTB with recovery factor 40.65%. 2. Scenario-2 (Base case + 2 Infilll well with constraint of 100 bbl/day), cumulative production obtained is 25.784 MSTB with recovery factor 42.06 %. 3. Scenario-3 (Base case + 2 Infill well with constraint of 1000 bbl/day), cumulative production obtained is 26.030 MSTB with recovery factor 42.46%. From 3 scenarios, scenario-3 has the highest recovery factor. From economic analysis, we obtain that scenario-3 gives IRR 16.88 % which is higher than assumed IRR 15%. NPV obtained is 4,906 M US$ and POT obtained is 3.71 years with profitability index equal to 1.11. In other words, project is commercially developed at those certain assumed crude oil price.